Drug Use Evaluation in the Pediatrics Admitted with Severe Respiratory Tract Infections - Vineela Chadalavada; Triveni P; Hameeda Begum Md; Pujitha S (Journal of Global Pharma Technology, 2020)
The objective of the present study is to evaluate drug prescribing patterns in children admitted with respiratory tract infections into pediatric ward. This is a prospective cross-sectional study conducted for a period of one year at a tertiary hospital located in a city of Andhra Pradesh, South India. The study was done by using prescribing indicators from the World health organization (WHO) manual for the conduction of drug use evaluation studies. The prevalence of respiratory tract infections, particularly lower respiratory tract infection is high among children less than 5 years. 54.39% of drugs are prescribed with brand names, of which the majority of drugs are administered through parenteral route (58.26%). Antibiotics (34.7%) are highly prescribed in all the cases followed by other category drugs. A significant difference was found in the evaluation of prescribed daily dose and standard dose. The profile of drug use in the present study was similar to previous Indian studies. Most of the prescribing encounters are parental forms and band names that need exploration of the present treatment trends. The present baseline data can serve for the development of national Pediatric prescribing guidelines in the future.